Policy of Spaing towards the Disputed Territories in the Western Mediterranean - Yu. A. Pavlova (Сравнительная политика, 2015)
On the basis of positivism and constructivism theories the article examines and analyzes the Spanish government’s point of view concerning the disagreement over the possession of Gibraltar, Ceuta and Melilla. The author has considered principal arguments of Spain in these territorial disputes that appear in the mass media, analytical articles and statements of different politicians concerned. The results of the research reveal the exact antithesis of the cases “Gibraltar” and “Ceuta and Melilla” in the context of positivism and constructivism theories.